If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6 + -7y) = 26 (6 * 8 + -7y * 8) = 26 (48 + -56y) = 26 Solving 48 + -56y = 26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -56y = 26 + -48 Combine like terms: 48 + -48 = 0 0 + -56y = 26 + -48 -56y = 26 + -48 Combine like terms: 26 + -48 = -22 -56y = -22 Divide each side by '-56'. y = 0.3928571429 Simplifying y = 0.3928571429
| -3-6n=-3(1+4n)+6n | | 4x+24=8x-12 | | 1.2d-6= | | 18=28+4(-5) | | 4x+7x+8+7x+2=172 | | -5n-5(-8n+3)=13+7n | | -7-4x=2x-7(1-7x) | | 2(5-x)-5x=3-(2+4) | | 5(2)5x=15 | | -5m=4-6m | | -5v-4+7v=-25 | | x+9+12x+7=159 | | -7(7n+5)=-280 | | 6y+3=13y-14 | | 12x-21=100+x | | 41=1+2n | | 2x+6x-7=1 | | 4n+19=6n-5(n+1) | | -18-2a=-9(5a-4) | | 21r=0 | | 12=3x+4*-9 | | -2(8-6r)=36-r | | 78-x=5x | | 1+7x=5+8x | | -5m+20=5(-4m+4) | | 6=-6(a-6)+3(a-5) | | 9=5x-2x | | 4v+5v=18 | | 4(-6x-3)=39-7x | | -9z+8+5=17 | | X^2-2=73 | | 7(1+7a)=a+7 |